Evaluating a Fistula Self-Care Bundle's Effect on Hemodialysis Patients’ Complications - Sahar A. Abdelmohsen; Hanan Abdelrazik Abdelall; Mohamed Hussein Ramadan Atta; Maha Nafady Abd El Hafez (SAGE Open Nursing)
Introduction Hemodialysis often leads to complications related to the arteriovenous fistula (AVF), the primary vascular access for dialysis. AVF complications, such as thrombosis and infection, are common and can disrupt treatment, increase morbidity, and diminish patients’ quality of life. Effective self-care and management of AVF are essential to minimize these risks, but many patients lack adequate knowledge and skills to perform necessary self-care practices. Objective To evaluate a fistula self-care bundle's effect on hemodialysis patients’ complications Methods Quasi-experimental design (study/control) study was conducted in the dialysis unit at Assiut University Hospital. Sample: A purposeful sample of sixty adult patients with an AVF on regular hemodialysis was assigned equally into two groups. Study tools: tool I; an interview questionnaire sheet to assess demographic data, medical history, tool II; patient complications assessment sheet, tool III; and a scale of assessment of self-care behaviors with AVF in hemodialysis. Findings Following the intervention, the overall self-care behavior score increased significantly ( p  = .000; d  = 1.79). Furthermore, specific behaviors such as washing the fistula arm, controlling fluid intake, and avoiding tight clothing showed significant improvements ( p  < .001). Importantly, there was a notable reduction in the frequency of complications such as infection, thrombosis, and steal syndrome in the study group post-intervention. Conclusion The findings demonstrated that the implementation of the fistula self-care bundle led to a significant reduction in vascular access complications among hemodialysis patients.